In Silico Study of Bioactive Compounds from Tangerines (Citrus reticulata) as Protein Inhibitor for 3CLpro SARS-CoV-2 : Omicron Variant - Victor Alvianoes Guterez Hose; Shella Zahra Kumala Azmi; Muhammad Faiz Maulana; Daniel Tumbur Hamonangan Sirait; Ailsa Calista Salsabila; Rahmat Grahadi; Fatchiyah Fatchiyah (JSMARTech, 2022)
COVID-19 is a disease caused by coronavirus that was identified as a new strain of coronavirus last December 2019. Coronavirus disease can be handled by blocking its protein using bioactive compounds, it is known that there are compounds from Citrus reticulata that have potential as antiviral. An in silico evaluation of the active compounds available in Citrus reticulata was carried out to compare their anti-inflammatory effects based on the molecular characteristics of docking with nirmatrelvir as a control compound. In addition, analysis of binding affinity, binding site, ADME prediction, and molecular dynamics simulation was also carried out. The results obtained indicate that neohesperidin compounds can bind to receptors that bind to catalytic sites on Cys145 and His41 as well as nirmatrelvir. In addition, there is also phlorin which can bind to the catalytic site of the His41 receptor. Active site analysis of the interaction suggests neohesperidin and phlorin compounds may have a therapeutic effect against COVID-19. However, from the results of ADME predictions, not all of these compounds qualify Lipinski's rule criteria such as neohesperidin and diosmin.